82‐4: Late‐News Paper: Characterization of metal thin film‐wiring materials for foldable devices. Issue 1 (29th May 2019) - Kura, Chiharu; Teramae, Yumi; Tauchi, Yuki; Goto, Hiroshi; Okuno, Hiroyuki
Abstract : Bending durability is a crucial issue associated with materials for foldable devices. To fabricate gate electrodes, high bending resistance and thermal resistance are important requirements for metal films. This report is on Al‐2.0at%Nd thin film, which exhibits excellent bending resistance and thermal stability, and is used to fabricate the gate electrodes for LTPS‐TFTs.